Analyzing the Effect of Inverter Efficiency Improvement in Wind Turbine Systems - Ozdemir, Sadik; Selamogullari, Ugur S.; Elma, Onur (IEEE, 2014)
This study presents the effect of efficiency improvement of wind turbine inverters-especially at low wind velocities-on generated wind energy. In order to present a detailed analysis, actual wind speed data is collected with one minute resolution in Istanbul, Turkey. The wind data is gathered at 10 meters and then projected to 30 meters. Technical data of a 20 kW wind turbine system is used to model the system and to calculate generated wind power. Data analysis shows that the wind turbine system needs to operate at low wind speed most of the time and wind turbine power electronic systems (inverters) should be designed accordingly to maximize wind potential. Case studies are completed to assess the effect of inverter circuit light load efficiency improvement on the energy yield.
Keywords: Wind turbine; Light load efficiency; Power inverter; Energy efficiency; POWER ELECTRONICS; Energy & Fuels